2014
DOI: 10.12659/msm.892111
|View full text |Cite
|
Sign up to set email alerts
|

Apo E Gene Polymorphism Affects Development of Type 2 Diabetic Nephropathy in Asian Populations, Especially in East Asians: An Updated Meta-Analysis

Abstract: BackgroundMany studies have determined the correlation between the Apolipoprotein E (APO E) gene polymorphisms and diabetic nephropathy, but their results are inconclusive.Material/MethodsWith the aim to confirm this correlation, we performed a meta-analysis of 16 studies. The dichotomous data are presented as the odds ratio (OR) with a 95% confidence interval (CI).ResultsThe results of our study indicate that APO ɛ2 allele among the pooled Asian populations were more likely to show high risk of DN development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the initial selection should be performed for the combinational results of GWAS and meta-analyses, along with genetic association with strong statistical support; at the same time, GWAS and metaanalyses showed convincing sizes effects are moderate in current platforms, as sample sizes can still explain the majority of large genetic risk for most common diseases (Zeggini & Ioannidis, 2009). Meta-analysis studies on the ApoE gene in relation to multiple diseases revealed both were positive (Arati et al, 2016;Cao et al, 2014;Garatachea et al, 2015;Gatt et al, 2015;Han et al, 2013;Li et al, 2015;Liao et al, 2014;Lin et al, 2014;Meng et al, 2013;Rubino et al, 2013;Sun et al, 2015;Wang et al, 2014;Yin et al, 2012;Yin et al, 2013;Yin et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Zhang et al, 2015), and negative associations (Agarwal & Tripathi, 2014;Gu et al, 2013;Liu et al, 2014;Miao et al, 2015;Stoumpos et al, 2013;Tian et al, 2014;Xu et al, 2015;Zhao et al, 2016;Zhu et al, 2016). Earlier reports in the nineties did not provide unequivocal conclusions regarding the relation of the ApoE gene and FH in different populations (Carmena et al, 1993;Friedlander & Leitersdorf, 1996;Utermann et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…However, the initial selection should be performed for the combinational results of GWAS and meta-analyses, along with genetic association with strong statistical support; at the same time, GWAS and metaanalyses showed convincing sizes effects are moderate in current platforms, as sample sizes can still explain the majority of large genetic risk for most common diseases (Zeggini & Ioannidis, 2009). Meta-analysis studies on the ApoE gene in relation to multiple diseases revealed both were positive (Arati et al, 2016;Cao et al, 2014;Garatachea et al, 2015;Gatt et al, 2015;Han et al, 2013;Li et al, 2015;Liao et al, 2014;Lin et al, 2014;Meng et al, 2013;Rubino et al, 2013;Sun et al, 2015;Wang et al, 2014;Yin et al, 2012;Yin et al, 2013;Yin et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Zhang et al, 2015), and negative associations (Agarwal & Tripathi, 2014;Gu et al, 2013;Liu et al, 2014;Miao et al, 2015;Stoumpos et al, 2013;Tian et al, 2014;Xu et al, 2015;Zhao et al, 2016;Zhu et al, 2016). Earlier reports in the nineties did not provide unequivocal conclusions regarding the relation of the ApoE gene and FH in different populations (Carmena et al, 1993;Friedlander & Leitersdorf, 1996;Utermann et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the Fabp4 and Pten gene expression and correlation in the liver, muscle, and adipose tissues of type 2 diabetes mellitus (T2DM) rats was shown to be increased, suggesting that the increased expression of PTEN and FABP4 may play an important role in the insulin resistance of T2DM [ 42 ]. In another study, the correlation between the Apolipoprotein E (APO E) gene polymorphisms and diabetic nephropathy was investigated, and it was suggested that development of diabetic neuropathy was associated with APO E polymorphisms in Asian populations [ 43 ].…”
Section: Discussionmentioning
confidence: 99%